PCR enables rapid detection of dermatophytes in practice - E. Aho-Laukkanen; V. Mäki-Koivisto; J. Torvikoski; S. P. Sinikumpu; L. Huilaja; I. S. Junttila (Microbiology Spectrum)
ABSTRACT Dermatophytes cause superficial infections of skin, hair, and nails. Even though they rarely cause severe infections, they are relatively common, particularly in primary health care. Diagnosis of dermatophyte infections has relied on relatively slow culture-based methods. Nucleic acid-based detection (PCR) methods might provide results more rapidly. Here, we describe the transition from culture-based methods into PCR-based methods in Northern Finland with a catchment area of approximately 720,000 mostly Caucasian people. This study included 14,330 samples collected between 2019 and 2022. Our results showed that the PCR-based method has become the diagnostic test of choice for these infections in this area. Commercial real-time PCR assay DermaGenius 2.0 complete multiplex test detected more positive results than culture and covered the most important dermatophytes, Candida albicans, and few less common species. With PCR, the mean turn-around-time from sample request to results decreased from 19 days to 16 hours.IMPORTANCESuperficial fungal infections, dermatophytosis, are remarkably common worldwide, affecting an estimated 20%–25% of the global population. In the diagnosis of these infections, fast and accurate results by PCR shorten the time to diagnosis and help clinicians to avoid unnecessary antifungal treatments.